Handbook of hygiene control in the food industry - Lelieveld, H. L. M. (Woodhead Publishing, 2011)
Developments such as the demand for minimally-processed foods have placed a renewed emphasis on good hygienic practices in the food industry. As a result there has been a wealth of new research in this area. Improving Hygiene in the Food Industry provides a comprehensive summary of the key trends and issues in food hygiene research.